Database resources of the National Center for Biotechnology Information. Issue Volume 47:Issue D1(2019) (5th November 2018) - Sayers, Eric W; Agarwala, Richa; Bolton, Evan E; Brister, J Rodney; Canese, Kathi; Clark, Karen; Connor, Ryan; Fiorini, Nicolas; Funk, Kathryn; Hefferon, Timothy; Holmes, J Bradley; Kim, Sunghwan; et al.
Abstract: The National Center for Biotechnology Information (NCBI) provides a large suite of online resources for biological information and data, including the GenBank ® nucleic acid sequence database and the PubMed database of citations and abstracts published in life science journals. The Entrez system provides search and retrieval operations for most of these data from 38 distinct databases. The E-utilities serve as the programming interface for the Entrez system. Augmenting many of the web applications are custom implementations of the BLAST program optimized to search specialized data sets. New resources released in the past year include PubMed Labs and a new sequence database search. Resources that were updated in the past year include PubMed, PMC, Bookshelf, genome data viewer, Assembly, prokaryotic genomes, Genome, BioProject, dbSNP, dbVar, BLAST databases, igBLAST, iCn3D and PubChem. All of these resources can be accessed through the NCBI home page atwww.ncbi.nlm.nih.gov .